Long-term safety of tofacitinib up to 9.5 years: a comprehensive integrated analysis of the rheumatoid arthritis clinical development programme - Peter Nash; Yoshiya Tanaka; Kevin L Winthrop; Eun Bong Lee; Xavier Mariette; Jeffrey R Curtis; Kenneth Kwok; Connie Chen; Pinaki Biswas; Lisy Wang; Christina Charles-Schoeman; Ann Madsen; et al. (RMD Open)
Objective Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). We report the largest integrated safety analysis of tofacitinib, as of March 2017, using data from phase I, II, III, IIIb/IV and long-term extension studies in adult patients with RA.Methods Data were pooled for patients with RA who received ≥1 tofacitinib dose. Incidence rates (IRs; patients with events/100 patient-years [PY]; 95% CIs) of first-time occurrences were obtained for adverse events (AEs) of interest.Results 7061 patients received tofacitinib (total exposure: 22 875 PY; median [range] exposure: 3.1 [0 to 9.6] years). IRs (95% CI) for serious AEs, serious infections, herpes zoster (all), opportunistic infections (excluding tuberculosis [TB]) and TB were 9.0 (8.6 to 9.4), 2.5 (2.3 to 2.7), 3.6 (3.4 to 3.9), 0.4 (0.3 to 0.5) and 0.2 (0.1 to 0.2), respectively. IRs (95% CI) for malignancies (excluding non-melanoma skin cancer [NMSC]), NMSC and lymphomas were 0.8 (0.7 to 0.9), 0.6 (0.5 to 0.7) and 0.1 (0.0 to 0.1), respectively. IRs (95% CI) for gastrointestinal perforations, deep vein thrombosis, pulmonary embolism, venous thromboembolism, arterial thromboembolism and major adverse cardiovascular events were 0.1 (0.1 to 0.2), 0.2 (0.1 to 0.2), 0.1 (0.1 to 0.2), 0.3 (0.2 to 0.3), 0.4 (0.3 to 0.5) and 0.4 (0.3 to 0.5), respectively. IR (95% CI) for mortality was 0.3 (0.2 to 0.3). IRs generally remained consistent across 6-month intervals to >78 months.Conclusion This represents the largest clinical dataset for a JAK inhibitor in RA to date. IRs remained consistent with previous reports from the tofacitinib RA clinical development programme, and stable over time.Trial registration numbers NCT01262118; NCT01484561; NCT00147498; NCT00413660; NCT00550446; NCT00603512; NCT00687193; NCT01164579; NCT00976599; NCT01059864; NCT01359150; NCT02147587; NCT00960440; NCT00847613; NCT00814307; NCT00856544; NCT00853385; NCT01039688; NCT02187055; NCT00413699; NCT00661661.For summary of phase I, phase II, phase III, phase IIIb/IV and LTE studies included in the integrated safety analysis, see online supplemental table 1.